Preliminary studies of biorefinery: Integration of slurry and CO2 gas as biomethane digester waste for microalgae Scenedesmus sp. growth - Hendroko Setyobudi, Roy; Kawaroe, Mujizat; Salafudin, Salafudin; Wahyudi, Ahmad; Maizirwan, Mel (Akademia Baru, 2017)
Bio-methane as renewable energy can generate slurry waste and CO2. Utilization of slurry has been examined in previous studies. Slurry digester which is made from seed cake Jatropha curcas, JatroMas cultivars can improve the growth of microalgae Scenedesmus sp. compared to standard media. CO2 gas as a biochemical process in the digester is the impurities to be minimized. A number of purification or enrichment technologies have been available for CO2 capture in order to improve the bio-methane quality. But adsorbs and / or chemical or physical absorption technology is relatively expensive. Microalgae reportedly are able to reduce CO2 levels in flue gas factory. Even the exhaust gas is spurring the microalgae growth. Related to this, a preliminary study has been conducted in ability of microalgae Scenedesmus sp. for CO2 capture in bio-methane. The study was conducted at the microalgae Laboratory of SBRC - IPB (Surfactantant Bioenergy Research Center - Bogor Agricultural University) Indonesia in March-April 2011. Scenedesmus sp. was cultivated in 1 000 mL erlenmeyer compared to standard medium as the control solution of 50 % slurry seed cake JatroMas cultivars. Bio-methane gas was inserted into the bottom of the erlenmeyer. Biomethane that came out from Scenedesmus sp. media was captured in the gas holder. Observation of Scenedesmus sp. growth curves has carried out in accordance, while medium levels of CO2 measurement is conducted with simple apparatus orsat. Studies were arranged in CRD, with three replications. The result showed that rate of Scenedesmus sp. growth in slurry is higher than the control for 0.10/day. The highest peak is in the seventh day of growth for 2.65 × 106 cells / mL. The average of bio-methane CO2 levels in slurry is lower than the control which is 21 % compared to 24 %. It can be concluded that the integration of slurry and CO2 gas waste from bio-methane digester that made from seed cake Jatropha curcas can spur Scenedesmus sp. growth.